Sit, stay, love - Howard, J. J. (Jennifer Jane), 1972- (Wish (Scholastic Inc.), 2016)
Before Cecilia Murray can adopt a cute pug named Potato, the arrogant, popular, but cute Eric Chung adopts the dog first. When Eric decides to turn Potato into a show-dog, Cecilia is horrified, and vows to sabotage his plans. However, as she spends more time with Potato and Eric, Cecilia realizes that she may have gotten Eric all wrong. She may even be falling for him.